Вплив наднаціональності на суверенітет держав-членів Європейського Союзу - Хоббі, Ю.С. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматривается проблема влияния принципа «наднациональности» Евросоюза на суверенитет его государств-членов и проблема распределения компетенции между ЕС и национальными правительствами. Учитывая попытки усиления евроинтеграции путем создания Конституции ЕС, возникла проблема сохранения национального суверенитета государств-членов ЕС. Taking into account the attempts of strengthening of the eurointegration by the creation of the EU' Constitution, the problem of saving the national sovereignty of the EU' states-members got up. In this connection the problem of influencing of the EU' principle of the «super-nationality» on the sovereignty of its states-members and the problem of distributing of jurisdiction between the EU and national governments are examined.